Positive effects of rutin on egg quality, lipid peroxidation and metabolism in post-peak laying hens - Zhang, Leizheng; Gong, Jiangang; Xi, Lin; Yang, Bowen; Hao, Yanshuang; Zhang, Haihua; Feng, Zhihua; Li, Qian (Frontiers in Veterinary Science, 2024)
Excessive fat deposition due to impaired fat metabolism in chickens is a major problem in the poultry industry. Nutritional interventions are effective solutions, but current options are limited. A safe phytochemical, rutin, has shown positive effects in animals, but its effect on lipid metabolism in poultry remains unknown. Hence, this study is to investigate the effects of rutin on egg quality, serum biochemistry, fat deposition, lipid peroxidation and hepatic lipid metabolism in post-peak laying hens. A total of 360 Taihang laying hens (49-week-old) were randomly divided into five groups and fed a basal diet (control group, 0%) and a basal diet supplemented with 300 (0.03%), 600 (0.06%), 900 (0.09%), and 1,200 (0.12%) mg rutin/kg feed, respectively. The results showed that eggshell strength was significantly (p < 0.05) higher in the dietary rutin groups, whereas yolk percentage (p < 0.05), total cholesterol (TC) (p < 0.01) and yolk fat ratio (p < 0.01) decreased linearly (p < 0.05) in the dietary rutin groups. Importantly, dietary rutin reduced serum triglyceride (TG) and TC levels, decreased abdominal lipid deposition and liver index (p < 0.05), and which concomitantly decreased hepatic lipid (TG, TC, and free fatty acid) accumulation (p < 0.05). An increase (p < 0.05) in total antioxidant capacity and superoxide dismutase activity and a decrease (p < 0.05) in malondialdehyde levels were also found. At the same time, the activities of hepatic lipase, acetyl-CoA carboxylase and malic enzyme in the liver were decreased (p < 0.05). Dietary rutin also increased (p < 0.05) the expression of fatty acid oxidation-related genes (carnitine palmitoyl transferase 1, peroxisome proliferator-activated receptor α, farnesoid X receptor). Additionally, it decreased fatty acid synthesis genes (sterol regulatory element binding protein-1c, acetyl-CoA carboxylase α, stearoyl-CoA desaturase 1) (p < 0.05). In conclusion, the addition of rutin (0.06–0.12%) to the diet improved the fat metabolism and increased liver antioxidant capacity in post-peak laying hens, and these positive changes improved egg quality to some extent.